Risk of Mycobacterium tuberculosis transmission in an antiretroviral therapy clinic. (23rd October 2018) - Mzembe, Themba; Mclean, Estelle; Khan, Palwasha Y.; Koole, Olivier; Sichali, Lifted; Mwinuka, Venance; Kayange, Michael; Mzumara, Peter; Dimba, Andrew; Crampin, Amelia C.; Glynn, Judith R.
Abstract : Objective: The risk of transmission of Mycobacterium tuberculosis in antiretroviral therapy (ART) clinics is recognized, particularly, when HIV and tuberculosis services are unified, but the degree of potential exposure to patients with infectious tuberculosis has not been measured. We aimed to quantify this clinic exposure. Methods: Over 1 year, we recorded all visits to a clinic in northern Malawi that offers HIV testing and counselling, HIV care, ART, and TB diagnostic and treatment services. We included patients and guardians, noting timing and reason for the visit, using a palm vein reader to assist recognition of individuals and record times automatically. Screening for tuberculosis was enhanced, including induced sputum if necessary. Results: Information was collected on 5011 individuals and 19 426 visits. During the period, 90 individuals with bacteriologically confirmed pulmonary tuberculosis attended the clinic when they were likely to have been infectious (taken as 6 weeks before diagnosis to 2 weeks after the start of treatment), including 76 who attended before tuberculosis was diagnosed or suspected. We estimated that 19% of visits had at least 1 h of potential exposure to patients with infectious tuberculosis, half to patients attending prediagnosis. Conclusion: There was considerable risk of exposure, including of immunosuppressed patients, to patients with infectious tuberculosis, especially as repeated visits are made. Much of this exposure could not be avoided by separation of patients with known tuberculosis. Good ventilation and avoidance of crowding is essential to minimize transmission of M. tuberculosis in this type of setting. Abstract : Supplemental Digital Content is available in the text